1996
DOI: 10.1007/bf02730917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of late orchidopexy is consistent with some undescended testes being acquired

Abstract: To diagnose the incidence of orchidopexy versus age over a 15-year period, a study was conducted of all patients discharged from a single institution for orchidopexy with reference to age during operation. The hypothesis drawn was that some boys have acquired UDT and therefore, will present late despite recommendations for early diagnosis and treatment. The study was conducted on patients from Royal Children's Hospital, Melbourne (1980-94). The results suggested that while the optimal age for management of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 9 publications
3
14
0
4
Order By: Relevance
“…Our studies suggest that not only are they common [50] but also that they are caused by failure of postnatal elongation of the spermatic cord [51]. At birth, the spermatic cord is 4 to 5 cm in length, but by the 10th year, it is 8 to 10 cm; this doubling in length is inhibited if there is a residual fibrous remnant of the PV, which may be caused by deficient CGRP release from the GFN postnatally [52].…”
Section: Cryptorchidism B: Acquiredmentioning
confidence: 82%
“…Our studies suggest that not only are they common [50] but also that they are caused by failure of postnatal elongation of the spermatic cord [51]. At birth, the spermatic cord is 4 to 5 cm in length, but by the 10th year, it is 8 to 10 cm; this doubling in length is inhibited if there is a residual fibrous remnant of the PV, which may be caused by deficient CGRP release from the GFN postnatally [52].…”
Section: Cryptorchidism B: Acquiredmentioning
confidence: 82%
“…In recent years evidence has been accumulating that late orchidopexy might be accounted for by acquired UDT [19][20][21][22][23]; several studies found that 40-70% of those undergoing orchidopexy had previously descended testes [24]. In addition, most boys undergo surgery when much older than usually recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between orchidopexy and cryptorchidism rates might partly reflect either misdiagnosed cases of retractile testes (Chilvers et al 1984;Cooper and Little 1985;Snick 1984) or the possibility that cryptorchidism is acquired after birth (Donaldson et al 1996;Jackson and John Radcliffe Hospital Cryptorchidism Research Group 1988), for which various etiologies have been postulated (Atwell 1985;Clarnette et al 1997;Hutson and Goh 1993;Rabinowitz and Hulbert 1997). The cremaster reflex cannot retract the testes from the scrotum to the superficial inguinal pouch until about 6 months of age (Cortes 1998).…”
Section: Discussionmentioning
confidence: 99%